FACTORS RELATED TO MATERNAL MANAGEMENT FOR CHILDREN WITH THALASSEMIA - อยู่สุข, ภัทร์ภร; สนั่นเรืองศักดิ์, ศิริยุพา; ธีระรังสิกุล, นฤมล (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2019)
The purposes of this correlational research were to examine maternal management for children with thalassemia and factors related to maternal management for children with thalassemia. The participants were 109 mothers of children with thalassemia who came to receive care at Short Stay Service in Ramathibodi hospital. Mothers who met the study inclusion criteria were randomly selected to participate in the study. Research instruments consisted of perceived severity of condition questionnaire, social support questionnaire and maternal management for children with thalassemia questionnaire. There reliabilities were .93, .94, and .82 respectively. Data was analyzed using descriptive statistic and Pearson’s product moment correlation coefficient. The results revealed that the maternal management in the dimension of the child’s daily life has a significant positive relationship with perceived severity of condition and social support (r = .202 and .191, respectively). The ability to manage the condition dimension has a significant positive relationship with perceived severity of the condition, duration of illness, age and social support (r = .181, .247, .226, and .147, respectively). The parental mutuality dimension has a significant positive relationship with family income and social support (r = .246 and .168). The impact of condition family life dimension has a significant negative relationship with perceived severity of condition, age, family income and social support (r = .282, .298, .262, and .230, respectively). The difficulty of family life dimension has a significant negative relationship with social support (r = -.261). The effort to manage the condition dimension has a significant negative relationship with social support (r = .254).